Negotiating the UN treaty on the prohibition of nuclear weapons and the role of ICAN. Issue 2 (4th May 2018) - Ruff, Tilman
ABSTRACT: The Treaty on the Prohibition of Nuclear Weapons is historic not only in its substance but in the process of its development. It was led by states free from nuclear weapons; based on humanitarian evidence and imperatives; involved civil society, hibakusha and survivors of nuclear testing to a degree that is unprecedented in the nuclear field; and is the first nuclear disarmament treaty negotiated through the UN General Assembly, with the process proving both effective and efficient, despite fierce opposition from a number of nuclear-armed states, whose lack of commitment to nuclear disarmament was made very plain. The International Campaign to Abolish Nuclear Weapons (ICAN) became the main civil society partner for governments leading and supporting the 'Humanitarian Initiative' which resulted in the negotiations. ICAN's principles, strategy and work are discussed in the context of the 'stigmatise – prohibit – eliminate' approach which has proven effective for other inhumane and indiscriminate weapons.